2017
DOI: 10.1038/srep43045
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin 3, ficolin-2 and lectin pathway associated serine protease MASP-3 as early predictors of myocardial infarction - the HUNT2 study

Abstract: The lectin complement pathway is suggested to play a role in atherogenesis. Pentraxin-3 (PTX3), ficolin-1, ficolin-2, ficolin-3, MBL/ficolin/collectin-associated serine protease-3 (MASP-3) and MBL/ficolin/collectin-associated protein-1 (MAP-1) are molecules related to activation of the lectin complement pathway. We hypothesized that serum levels of these molecules may be associated with the incidence of myocardial infarction (MI). In a Norwegian population-based cohort (HUNT2) where young to middle-aged relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The following lectin pathway pattern recognition molecules were measured in both plasma and BAL in duplicate: MBL, PTX3, FCN-1, FCN-2, and FCN-3 were quantified in specific sandwich ELISAs with monoclonal antibodies for each marker developed in the Laboratory of Molecular Medicine, Rigshospitalet, according to previously described procedures ( 57 61 ). All assays were optimized for automated analysis in a 384-well format on the Biomek FX robotic system (Beckman Coulter) ( 62 ). Alternative assays for C4 activation, i.e., C4c and sC5b-9 (TCC) were measured in ELISAs based on monoclonal antibodies against neoepitopes on the C4c fragment and C9 not exposed on the native molecules as described previously ( 63 , 64 ).…”
Section: Methodsmentioning
confidence: 99%
“…The following lectin pathway pattern recognition molecules were measured in both plasma and BAL in duplicate: MBL, PTX3, FCN-1, FCN-2, and FCN-3 were quantified in specific sandwich ELISAs with monoclonal antibodies for each marker developed in the Laboratory of Molecular Medicine, Rigshospitalet, according to previously described procedures ( 57 61 ). All assays were optimized for automated analysis in a 384-well format on the Biomek FX robotic system (Beckman Coulter) ( 62 ). Alternative assays for C4 activation, i.e., C4c and sC5b-9 (TCC) were measured in ELISAs based on monoclonal antibodies against neoepitopes on the C4c fragment and C9 not exposed on the native molecules as described previously ( 63 , 64 ).…”
Section: Methodsmentioning
confidence: 99%
“…These two studies illustrated a significant relation between PTX3 levels and cardiovascular mortality and all-cause death (60, 61). In addition, it was recently shown that higher PTX3 levels predicted occurrence of MI in a cohort of young or middle-aged individuals followed for a first-time MI (62).…”
Section: Ptx3 In Cvdmentioning
confidence: 99%
“…Ischemic heart disease and stroke have been the leading causes of death globally in the past decades, and the mortality rate from these diseases is gradually increasing. In addition to traditional cardiovascular (CV) risk factors such as smoking, type 2 diabetes mellitus (T2DM), hypertension (HTN) and dyslipidemia, researchers have investigated potential novel biomarkers, for instance, copeptin 1 , pentraxin-3 2 and heart-type fatty acid binding protein (H-FABP) to predict the clinical course and CV outcomes. In particular, H-FABP has been widely studied in patients with acute coronary syndrome (ACS), and it has been suggested to increase diagnostic sensitivity and possibly predict long-term survival 3 .…”
Section: Introductionmentioning
confidence: 99%